Hepatic inflammatory pseudotumor in childhood: A case report (Research, Society and Development, 2025)
Inflammatory pseudotumor of the liver (PIF) presents as a type of rare, benign lesion, without neoplastic characteristics, and may arise from an exacerbated inflammatory response to some form of aggression, such as infections, trauma, or autoimmune conditions, and in some situations, can mimic malignant tumors, leading to a complex diagnosis, often late and differentiated. Clinically, it may present as a hepatic mass or hepatic abscess, which complicates the initial diagnosis. Thus, the final diagnosis requires histopathological examination and biopsy, as its conclusive study can resemble other types of liver lesions. Objective: To report a case of a 12-year-old patient, previously healthy, with fever for 11 days, associated with vomiting, abdominal pain in the right hypochondrium, initially to clarify until his diagnosis of inflammatory pseudotumor of the liver and clinical outcome. Methods: The data were obtained through electronic medical records and printed. The study was approved by the Research Ethics Committee at the hospital of origin and authorized by the legal guardians through the Informed Consent Form (ICF). This is an observational and descriptive study, without a control group, in the format of a clinical case report. Results/Conclusion: The pseudotumor should be considered in the differential diagnosis of any liver lesion, as initial examinations lead to suspicion of neoplastic conditions.